High energy photobiomodulation therapy in the early days of injury improves sciatic nerve regeneration in mice - Souza, Luana Gabriel de; Cardoso, Ramon Bauer; Kuriki, Heloyse Uliam; Marcolino, Alexandre Márcio; Fonseca, Marisa de Cássia Registro; Barbosa, Rafael Inácio (ABCS Health Sciences, 2020)
Introduction: Different studies have evaluated the effects of electrophysical agents on regeneration after peripheral nerve injury. Among them, the most used in clinical and experimental research is photobiomodulation therapy (PBMT). Objective: To analyze the effect of standard energy (16.8 J) of PBMT on peripheral nerve regeneration, applied at different periods after sciatic nerve injury in mice. Methods: Thirty male Swiss mice were divided into six groups: naive; sham; control; LLLT-01 (660 nm, 16.8 J of total energy emitted in 1 day); LLLT-04 (660 nm, 4.2 J per day, 16.8 J of total energy emitted in 4 days); LLLT-28, (660 nm, 0.6 J per day, 16.8 J of total energy emitted over 28 days). The animals were evaluated using thermal hyperalgesia, Sciatic Functional Index (SFI), and Static Sciatic Index (SSI). Data were obtained at baseline and after 7, 14, 21, and 28 days after surgery. Results: For the SFI and SSI, all groups showed significant differences compared to the control group, and the LLLT-04 group presented the best results among those receiving PBMT. In the assessment of thermal hyperalgesia, there was a significant difference in the 14th day of evaluation in the LLLT-04 group. Conclusion: The application of 16.8 J was useful in sciatic nerve regeneration with an improvement of hyperalgesia, with higher efficacy when applied in four days (4.2 J/day).